Non complicated esophagitis caused by reflux - Praderi, Luis A; Balboa, Oscar (Cirugía del Uruguay, 1984)
Authors present their experience in treating 107 patients suffering from esophagitis caused by reflux, having conditioned no estenosis, ulcers or shortening of the esophagus.